Prolonged SARS-CoV-2 infection associated with long-term corticosteroid use in a patient with impaired B-cell immunity - Morishita, Momoko; Suzuki, Manabu; Matsunaga, Akihiro; Ishizhima, Keishi; Yamamoto, Tsukasa; Kuroda, Yudai; Kanno, Takayuki; Tsujimoto, Yoshie; Ishida, Akane; Hashimoto, Masao; Ishii, Satoru; Takasaki, Jin; et al. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2022)
Corticosteroids are widely used to treat severe COVID-19, but in immunocompromised individuals, who are susceptible to persistent infection, long term corticosteroid use may delay viral clearance. We present a case of prolonged SARS-CoV-2 infection in a man with significantly impaired B-cell immunity due to non-Hodgkin lymphoma which had been treated with rituximab. SARS-CoV-2 shedding persisted, despite treatment with remdesivir. Viral sequencing confirmed the persistence of the same viral strain, ruling out the possibility of reinfection. Although SARS-CoV-2 IgG, IgA and IgM remained negative throughout the treatment period, after reduction of the corticosteroid dose, PCR became negative. Long-term corticosteroid treatment, especially in immunocompromised individuals, may result in suppression of cell-mediated immunity and prolonged SARS-CoV-2 infection.